1997
DOI: 10.1007/bf01628504
|View full text |Cite
|
Sign up to set email alerts
|

The sensory innervation of the hip joint - an anatomical study

Abstract: Typically obturator nerve blockade is used to relieve hip pain. It sometimes only has a minor effect in resolving symptoms. This clinical observation led us to examine comprehensively the sensory nerve innervation of formalin-fixed hip joint capsules. Following macroscopic preparation, the area of the hip joint capsule was inspected with the aid of an operating microscope. We discovered a separation between the anterior and posterior sensory innervation of the hip joint capsule. The anteromedial innervation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
211
1
9

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(222 citation statements)
references
References 4 publications
1
211
1
9
Order By: Relevance
“…The mechanism whereby L1/L2 block provides analgesia of the hip joint is less clear, as the nerve supply to the hip joint is complex, is often variable, and has been a source of debate. An elegant anatomical study by Birnbaum et al [6] showed that the anterior and posterior parts of the joint capsule have different sensory innervations. The anterior part of the joint capsule is innervated by articular branches of the femoral nerve, and the anteromedial part is innervated by articular branches of the obturator nerve.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism whereby L1/L2 block provides analgesia of the hip joint is less clear, as the nerve supply to the hip joint is complex, is often variable, and has been a source of debate. An elegant anatomical study by Birnbaum et al [6] showed that the anterior and posterior parts of the joint capsule have different sensory innervations. The anterior part of the joint capsule is innervated by articular branches of the femoral nerve, and the anteromedial part is innervated by articular branches of the obturator nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the mechanism of OA pain has been considered to be of nociceptive origin, but our study identified 5.9% of our hip OA patients as likely to have NP. Regarding the mechanism of NP in hip OA, we have formulated the hypothesis that NP occurs in association with damage to nerves innervating subchondral bone [22], ligamentum capitis femoris [23], capsule [23][24][25]27], the soft tissues of the fossa acetabuli [24], labrum [26] or synovial membrane [27]. Torrance et al [28] reported the results of an epidemiological survey in the UK using S-LANSS [29], the selfcompleted version of the Leeds Assessment of Neuropathic Symptoms and Signs pain scale [30].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, overall good agreement existed concerning the assessment of the treatment effect, and the clinical examination by and large confirmed the findings reported by the patients. The effect of pain relief was graded from 0 ( = no pain relief) to 1 = mild pain relief; 2 = good pain relief 3 = excellent pain relief (no more pain) Pain during the block was graded from 0 = no pain/discomfort to 1 = mild pain/discomfort; 2 = some pain; 3 = significant pain a On the day of the block b During the time indicated in the right column Table 4 Clinical assessment after treatment according to the Merle d'AubignØ score [12]. See Table 2 …”
Section: Resultsmentioning
confidence: 99%
“…Lacking effect of pain relief despite correctly placed blocks may be explained by the fact that innervation of the hip varies [11, 12,16] or by the fact that (depending on the type of osteoarthritic changes) a slightly different position of the femoral head within the joint may not lead to reduced pain in an individual case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation